Controllable synthesis of La3+ doped Zn0.5Co0.25Cu0.25Fe2−xLaxO4 (x = 0.0, 0.0125, 0.025, 0.0375, 0.05) nano-ferrites by sol-gel auto-combustion route. Issue 18 (15th December 2020) - Rehman, Atta Ur; Morley, N.A.; Amin, Nasir; Arshad, Muhammad Imran; un Nabi, Muhammad Ajaz; Mahmood, Khalid; Ali, Adnan; Aslam, Asma; Bibi, Aisha; Iqbal, Muhammad Zahir; Iqbal, Faisal; Bano, N.; et al.
Abstract: Z n 0.5 C o 0.25 C u 0.25 F e 2 − x L a x O 4 ( x = 0.0, 0.0125, 0.025, 0.0375, 0.05) ferrite powders with uniform distribution of ions and close-packed configuration were prepared via sol-gel auto-combustion route. XRD spectra showed the formation of spinel-phase cubic crystalline structure. SEM results revealed that the irregularity in size and shape of particles increases, and particle distribution uniformity decreases with La 3+ concentration. Moreover, each curve of the UV–vis spectra revealed two optical energy band gaps. More importantly, DC resistivity ( ρ ) and the activation energy ( Δ E ) have minimum values at x = 0.0375. The dielectric loss was explained according to Maxwell-Wager space charge polarization. The P-E loop showed the ferroelectric nature of the synthesized samples. Moreover, VSM results revealed that the as-prepared samples possessed maximum saturation magnetization ( M S = 56.77 ± 0.0283) and 8–12 GHz operating microwave frequency ( ω m ) range at x = 0.0375. All these results show the potential of Z n 0.5 C o 0.25 C u 0.25 F e 1.9625 L a 0.0375 O 4 ferrite powders for X-band microwave applications. Graphical abstract: Image 1 Highlights: Zn0.5 Co0.25 Cu0.25 Fe2-x Lax O4 ferrite powders via simple sol-gel auto-combustion. Crystallite size and lattice constant decrease with increasing La 3+ cations. Optical band gap energies and DC resistivity have minimum values at x = 0.0375. The ferroelectric nature of all the samples was confirmed using the P-E loop. Maximum magnetization saturation was observed at x = 0.0375.